2006
DOI: 10.1007/s10549-006-9190-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1α correlates with VEGF-C expression and lymphangiogenesis in breast cancer

Abstract: The transcription factor Hypoxia inducible factor-1alpha (HIF-1alpha) plays a crucial role in tumor progression by regulating angiogenesis, cell survival and drug resistance. HIF-1alpha is also implicated in biological functions under normoxic conditions and recent data provide evidence for a possible role in tumor lymphangiogenesis by regulating the lymphatic vascular endothelial growth factor-C (VEGF-C). In breast cancer, lymphatic vessel invasion (LVI) by tumor cells and subsequent metastasis to axillary ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 32 publications
5
65
0
5
Order By: Relevance
“…Previous descriptive studies reported correlations between HIF-1α expression and VEGF-C, FGF-2, and PDGF-B in breast cancer (12,20), gastric carcinoma (21), squamous cell carcinoma (14,17), and mesothelioma (31). Importantly, HIF-1α levels had prognostic value in LN-negative breast carcinomas (13).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous descriptive studies reported correlations between HIF-1α expression and VEGF-C, FGF-2, and PDGF-B in breast cancer (12,20), gastric carcinoma (21), squamous cell carcinoma (14,17), and mesothelioma (31). Importantly, HIF-1α levels had prognostic value in LN-negative breast carcinomas (13).…”
Section: Discussionmentioning
confidence: 89%
“…Clinical studies have found that increased HIF-1α levels in primary breast tumors are significantly associated with peritumoral LV density (12) and patient mortality (13). HIF-1α levels also were associated with LN metastasis in esophageal cancer (14).…”
mentioning
confidence: 99%
“…The present study also demonstrated the correlation between both VEGF-C and VEGF-A to LVD and MVD, thus suggesting the two growth factors to be involved in both angiogenesis and lymphangiogenesis. On the other hand, the HIF-1· expression was demonstrated to correlate with the VEGF-C expression and lymphatic microvessel density in breast cancer (73) and oral squamous cell carcinoma (74). These findings suggested that Akt activation also contributes to lymphangiogenesis via VEGF-A and -C and HIF-1· expression.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Several previous reports have shown that HIF-· correlates with metastasis and distant recurrence (12)(13)(14)(15) and also correlates with VEGF-C expression and lymphangiogenesis in breast cancer (41). Therefore, we hypothesize that Tß4 may help regulate the process of lymph node metastasis due to its strong correlation with HIF-· expression.…”
Section: (77) -------------------------------------------------mentioning
confidence: 70%